Parental stress and its dimensions in Neonatal -Pediatric Intensive Care Units: Narrative Review - Peña Silva, Beatriz (2021)
The hospitalization of a minor is a stressful event for the entire family group, where parents are more affected due to the alteration of their role. Objective: To determine the level of stress and dimensions that most affect the parents of minors hospitalized in Units of Neonatal-Pediatric Intensive Care and the description of interventions for its reduction. Method: The bibliographic search was carried out in the Web of Science, Scopus, Virtual Health Library, EBSCO and SciELO databases. The descriptors used were "psychological stress", "intensive care units" and "parents". Initially, 250 articles were selected, of which 214 were discarded by exclusion criteria. After critical reading of 35 articles, 17 were finally selected. Main Results: The experience of hospitalization of a son or daughter in these units is stressful for the parents. where a moderate level of stress is mostly seen in the parents, where the difference between the sexes is not significant. The most stressful dimensions were the alteration of the parental role and appearance and behavior of the baby, finding successful interventions to reduce parental stress. General Conclusions: there is a shortage of research in Pediatric Intensive Care Unit, being interesting to study in depth the cultural characteristics of parental stress. The nursing professional must take care of the parents as part of their work, through interventions such as empathic communication and favoring their active participation, allowing parents to participate in some care of their son or daughter.